Characterising restrictions on commercial advertising and sponsorship of harmful commodities in local government policies: a nationwide study in England. - McKevitt, Sarah; White, Martin; Petticrew, Mark; Summerbell, Carolyn; Vasiljevic, Milica; Boyland, Emma; Cummins, Steven; Laverty, Anthony A.; Millett, Christopher; de Vocht, Frank; Junghans, Cornelia; Vamos, Eszter P (Journal of Public Health, 2023)
Background Commercial advertising and sponsorship drive the consumption of harmful commodities. Local authorities (LAs) have considerable powers to reduce such exposures. This study aimed to characterize local commercial policies across all English LAs. Methods We conducted a census of all English LAs (n = 333) to identify local commercial policies concerning advertising and sponsorship of tobacco, alcohol, less healthy foods and gambling, through online searches and Freedom of Information requests. We explored policy presence, commodity frequency and type, and associations with LA characteristics (region, urban/rural and deprivation). Results Only a third (106) of LAs in England had a relevant policy (32%). These included restrictions on tobacco (91%), gambling (79%), alcohol (74%) and/or less healthy foods (24%). Policy prevalence was lowest in the East of England (22%), North East (25%) and North West (27%), higher in urban areas (36%) than rural areas (28%) and lower in the least (27%) compared with the most (38%) deprived areas. Definitions in policies varied, particularly for alcohol and less healthy foods. Conclusions English LAs currently underutilize their levers to reduce the negative impacts of harmful commodity industry marketing, particularly concerning less healthy foods. Standardized guidance, including clarity on definitions and application, could inform local policy development.